Infrastructure for peace: Conflict settlement between pastoralists and farmers in Kilosa/Tanzania - Schetter, Conrad; Massoi, Lucy; Shillingi, Venance (Journal of Eastern African Studies, 2026)
Paper submitted for publication in the Journal of Eastern African Studies